2018
DOI: 10.1039/c7ce01691c
|View full text |Cite
|
Sign up to set email alerts
|

Growth of mixed-halide perovskite single crystals

Abstract: The graph shows the mixed-halide crystals of CH3NH3PbI3−xBrx and CH3NH3PbBr3−yCly grown by the ITC method using mixed organic solvents.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
42
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(50 citation statements)
references
References 26 publications
8
42
0
Order By: Relevance
“…A similar shift was also reported for mixed-halide lead-based perovskite single crystals. 36 As illustrated in the AFM topographical map (Fig. 3(a)) on the (002) face of the C3 bulk single crystal, the perovskite material reveals a terrace feature with two-dimensional parallel large quantum well planes.…”
Section: Crystal Growthmentioning
confidence: 97%
“…A similar shift was also reported for mixed-halide lead-based perovskite single crystals. 36 As illustrated in the AFM topographical map (Fig. 3(a)) on the (002) face of the C3 bulk single crystal, the perovskite material reveals a terrace feature with two-dimensional parallel large quantum well planes.…”
Section: Crystal Growthmentioning
confidence: 97%
“…Inverse temperature crystallisation (ITC) is method which takes advantage of the observed retrograde solubility of perovskites, allowing rapid growth of high-quality, millimetre-sized perovskites in a matter of days. 7,12,13 Based on the ITC approach single crystal materials of MAPbX 3 (MA ¼ methylammonium and X ¼ halide), 7,13,14 FAPbX 3 (FA ¼ formamidinium), 12,15,16 CsPbBr 3 , [17][18][19] MAPbBr 3Àx Cl x , [20][21][22][23] MAPbBr 3Àx I x 21,[23][24][25][26] and heterovalent doped MAPbBr 3 27 and MAPbCl 3 28 have been reported. It has been shown that substitution of MA for FA can lead to improved stability in solar cells 29 and enhanced charge transport properties in thin lms 30,31 and single crystals 16 compared to their MAPbX 3 counterparts.…”
Section: Introductionmentioning
confidence: 99%
“…The growth of MAPbX n Y 3-n single crystals is of key importance for the advancement of perovskitebased applications, as well as for gaining an understanding of their fundamental properties. Typically, lead halide perovskites are synthesized from their precursor solutions by film preparation 18,19 , a solvothermal approach 20 , or controlling retrograde solubility 16,[21][22][23] . However, these methods lead to the initiation of multiple nucleation sites and the formation of several small crystals.…”
Section: Introductionmentioning
confidence: 99%